Observation Study of Business Capital Factors, Business Location, and Marketing Strategies on the Succes of Culinary MSME Business in Dumai City - Monica Putri; Wan Junita Raflah (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2022)
This study aims to determine the factors of venture capital, business location and marketing strategy on the success of MSME businesses in Dumai City. In this study, the author focuses his research on culinary SMEs. The type of research used is observational with a quantitative approach. The variables in this study include business capital, business location, marketing strategy and business success. The population in this study are people who have culinary businesses. The sample used in this study was 100 respondents who were taken by purposive sampling technique and the data collection method used a questionnaire. Analysis of the data used isdescriptive analysis. The results of this study indicate that the dominant factor of venture capital on business success with an average indicator of 3.22 with a medium category. The dominant factor of business location on business success with an average indicator of 4.08 in the high category. The dominant factor of marketing strategy on business success with an average indicator of 3.91 in the high category. And the dominant factor of business success with an average indicator of 3.51 in the high category.